Vitamin D deficiency is associated with high prevalence of diabetes in Kuwaiti adults: results from a national survey. (December 2015) - Zhang, Fang; Al Hooti, Suad; Al Zenki, Sameer; Alomirah, Husam; Jamil, Kazi; Rao, Aravinda; Al Jahmah, Nasser; Saltzman, Edward; Ausman, Lynne M.
Abstract Background Vitamin D homeostasis may play a critical role in glucose metabolism. Little is known on vitamin D deficiency and its association with diabetes in countries of the Arabia Gulf where the population is experiencing a rapid increase in the incidence of diabetes. Methods In a cross-sectional study of 960 adults enrolled in the first National Nutrition Survey of the State of Kuwait (NNSSK), we examined vitamin D status in association with the prevalence of diabetes and prediabetes. Vitamin D status was measured by serum levels of 25-hydroxyvitami D (25(OH)D). Prevalences of diabetes and prediabetes were determined based on fasting glucose and HbA1C levels. Results The median level of serum 25(OH)D in Kuwaiti adults was 13.8 ng/ml. Approximately 56 % of the Kuwaiti adults had vitamin D inadequacy (25(OH)D = 12–19.9 ng/ml), and 27 % had vitamin D deficiency (25(OH)D < 12 ng/ml). The prevalences of prediabetes and diabetes were 40 and 27 %, respectively. Vitamin D inadequacy (OR = 1.7, 95 % CI: 1.0–2.9) and deficiency (OR =2.0, 95 % CI: 1.1–3.3) was each associated with about two-fold increased odds of prediabetes compared to sufficient vitamin D status (25(OH)D ≥20 ng/ml). Vitamin D inadequacy (OR =2.1, 95 % CI: 1.2–3.7) and deficiency (OR =2.0, 95 % CI: 1.1–3.9) were also associated with two-fold increased odds of diabetes. Conclusions Data from Kuwaiti's first nutrition nutritional survey suggests a very high prevalence of vitamin D deficiency in Kuwaiti adults. Associations of low vitamin D status and high prevalence of diabetes point to the need of continuous monitoring of vitamin D status and further evaluating potential health consequences in this high-risk population.